20 Years is nothing. Revisiting Tapera Moreira Archaeological Locality, Province of La Pampa, Argentina - Beron, Monica Alejandra; Carrera Aizpitarte, Manuel Pedro; Paez, Florencia Natalín; Lucero, Eliana Noelia; Bedran, Sofia Florencia (Springer, 2024)
The Tapera Moreira archaeological locality is composed of five sites with different characteristics. It is located on the banks of the Curacó River, in the south-central sector of the province of La Pampa, Argentina. This set of sites represents the occupational redundancy of this landscape, ranging from the Middle Holocene to the final Late Holocene (ca. 4550-360 years BP) and constitutes the main chronological-cultural sequence of the Curacó area. This locality was investigated in two stages, the first between 1988 and 1995 and the second from 2015 to the present. Excavations were reopened at site 1 and a new burial was located at site 3. The objectives of this paper are to present the results of the new excavations, and then integrate these results with the previous ones (1988-1995) to assess patrons, trends and differences. The data generated allows us to evaluate the trajectories and social interactions of hunter-gatherer populations on a macro-regional scale, as well as the mobility circuits and the interaction networks throughout a wide area that covers both oceans and from 36° to 40° LS. This information integrated with the knowledge generated in neighboring regions allows us to outline a panorama of the social and cultural dynamics of the last 5.000 years.